Atomically dispersed Co-Cu dual active sites in carbon networks as an efficient oxygen electrocatalyst - Sinha, Nibedita; Das, Chandni; Pal, Santanu; Urkude, Rajashri R.; Ahmed, Tanbir; Ghosh, Biplab; Roy, Poulomi (Dalton Transactions, 2025)
Single-atom metal-based electrocatalysts offer extended advantages by maximizing the utilization of active sites but often suffer from complex synthesis processes and low-density metal loading. The present work showcases a strategic design for integrating highly dense cobalt-copper dual atoms dispersed on a nitrogen-rich porous carbon network (CoCu-NGC). The atomically dispersed CoCu-NGC outperforms the ORR and OER activities of their single metallic counterparts (Co-NGC or Cu-NGC) and conventional noble-metal based electrocatalysts (Pt/C and RuO2). Benefitting from the electronic modulation in the dual SAC system, the CoCu-NGC displayed outstanding bifunctional performance with low Delta E values of 0.69 V in freshwater and 0.78 V in seawater, highlighting it as a potential alternative to the costly state-of-art electrocatalysts.

Chlorophobic iron hydrogen phosphite as OER-active electrocatalyst in anion exchange membrane (sea)water electrolysis - Das, Chandni; Sinha, Nibedita; Nair, Aathira; Pal, Santanu; Joshi, Kavita; Roy, Poulomi (Small, 2025)
Seawater electrolysis is recognized as a promising technology to cater to the worldwide drive for sustainable hydrogen production; however, its practical viability is often hindered by the inevitable anode corrosion arising from the electrode side reactions owing to the presence of high chloride content which eventually degrade the electrode performance eventually. Herein, the design of unprecedented ammonium iron hydrogen phosphite (FeHPhi) along with a trace amount of Cu, is reported as the unique and much desired electrode material for seawater electrolysis due to its special chloride repellant nature along with great electrocatalytic activity toward water oxidation. The [HPO3](2-) oxoanion as Lewis base in the structure effectively restricts chloride ions, while the Fe center acts as Lewis acid offering an active site for water oxidation, also well-supported theoretically. Leveraging this frustrated Lewis pair combination, the electrocatalyst achieves a high current density of 500 mA cm(-2) at 344 mV overpotential in alkaline real seawater with impressive robustness to sustain for 200 h when operated under chlorine evolution reaction dominating region (>2 V). The electrocatalyst also demonstrates superior performance in anion exchange membrane freshwater and seawater electrolysis, demonstrating its potential applicability.
Keywords: AEM electrolyzer; chloride repellant; electrocatalyst; hydrogen production; seawater oxidation

Energy-saving H2 production through H2S electrolysis accompanying solid sulfur recovery using a Ni3S2/Ni3N heterostructure as the electrocatalyst - Sinha, Nibedita; Das, Chandni; Pal, Santanu; Roy, Poulomi (ACS Applied Energy Materials, 2025)
The thermodynamically feasible electrochemical sulfion oxidation reaction (SOR) is advantageous for degrading the toxic H2S pollutant into the value-added chemical sulfur but often suffers from catalyst passivation due to blockage of electroactive sites by accumulation of solid sulfur. The strategic design of electrocatalysts with enhanced electrochemical activity and improved sulfur tolerance is thereby crucial to fully harness the benefits of the SOR. In this work, we developed nickel sulfide nanorods decorated with nickel nitride nanoparticles directly grown on conductive nickel foam as an efficient trifunctional electrocatalyst for the SOR, oxygen evolution reaction (OER), and hydrogen evolution reaction (HER). Optimized Ni3S2/Ni3N showed lower electrode potentials of 0.25, 1.487, and 0.89 V to achieve a benchmark current density of 10 mA cm(-2) for the SOR, OER, and HER, respectively. The hybrid H2S electrolysis setup employing a Ni3S2/Ni3N electrocatalyst drastically reduced the cell potential by 1.24 V compared to that of conventional water electrolysis at a current density of 200 mA cm(-2). Having said that, heterostructure formation not only enhances the activity for the SOR but also helps to avoid sulfur poisoning, enabling the electrocatalyst to sustain for 100 long hours at a high current density of 100 mA cm(-2). Consequently, the approach with the developed electrocatalyst has the ability to reduce the energy consumption by 59.22%, which can make rigorous, economically viable H-2 production driven by solar energy.
Keywords: energy-economic; H-2 production; H2S electrolysis; heterostructure; solidsulfur

Enhanced electrocatalytic performances of NiCr layered double hydroxides by oxalate intercalation in anion exchange membrane water electrolysis - Pal, Santanu; Sinha, Nibedita; Das, Chandni; Chauhan, Inderjeet; Ahmed, Tanbir; Roy, Poulomi (ACS Applied Materials & Interfaces, 2025)
Layered double hydroxides (LDHs) have attracted much attention these days in the field of water electrolysis due to easy modulation in their layered structure and properties. Herein, NiCr-LDH has been developed, and its interlayer spacing has been considerably increased by oxalate intercalation. Such increased interlayer spacing allows easy access of hydroxides to a large number of electroactive sites and thereby boosts the electrocatalytic performances both for oxygen and hydrogen evolution reactions. Being very active toward both the electrocatalytic reactions, the oxalate-intercalated NiCr-LDH was further explored in an alkaline anion exchange membrane water electrolyzer (AEMWE), achieving 800 mA cm-2 at 1.88 V cell voltage at an operating temperature of 60 degrees C. In fact, the electrolyzer efficiency has been determined to be as high as 69.66%, and the calculated H2 production cost was found to be \$0.97 per gasoline-gallon equivalent, which is well below the targeted cost by the Department of Energy, USA. The electrocatalyst was also examined in harsh alkaline media, like highly saline or seawater, which also indicated its ability to carry out sustainable seawater electrolysis, restricting chlorides to a great extent. Interestingly, post-electrolysis characterization reveals the fact that oxalate decomposition aided carbonate formation within interlayers of NiCr-LDH, and high affinity toward hydroxides is responsible for restricting chlorides during the electrolysis process, apart from the great electrocatalytic activity.
Keywords: Anion exchange; hydrogen production; interlayerspacing; Layered double hydroxide; Sustainable; water electrolyzer

NiFeMo layered triple hydroxide and MXene heterostructure for boosted oxygen evolution reaction in anion exchange membrane water electrolysis - Pal, Santanu; Chaturvedi, Ekta; Das, Chandni; Sinha, Nibedita; Ahmed, Tanbir; Roy, Poulomi (Nanoscale, 2025)
Efficient, low cost and stable electrocatalysts are highly desirable for overcoming the sluggish kinetics of the oxygen evolution reaction (OER) in alkaline water electrolysis for hydrogen production. Interfacial engineering of heterostructures is quite beneficial for improving charge transfer efficiency at the interface. In this context, heterostructures of layered triple hydroxides (LTHs) and MXenes have shown great potential as OER electrocatalysts owing to their 2D-2D structure and unique physiochemical properties. Coupling LTHs with MXenes can potentially enhance their conductivity and stability, thereby boosting OER activity. In this study, we report a heterointerface between NiFeMo-LTH on Ti3C2Tx MXene, which exhibited superior catalytic activity and stability in alkaline freshwater and seawater, reducing the activation energy. Importantly, the heterostructure achieved a current density of 100 mA cm-2 at the cost of 292 mV and 340 mV overpotentials in alkaline saline water and real seawater, respectively, and showed robustness over 100 h without hypochlorite formation in alkaline real seawater, exhibiting corrosion-resistant behaviour. Moreover, NiFeMo-LTH/MXene explored in alkaline anion exchange membrane water electrolyzer (AEMWE) achieved a current density of 750 mA cm-2 at 2.16 V cell voltage at an operating temperature of 60 degrees C with an energy efficiency of 60.5%. Raman analysis and XPS analysis post stability test demonstrated easy electron transfer from LTH to MXene at the heterointerface, leading to the formation of NiOOH electroactive species that facilitated the OER activity.

Amorphous vanadium-doped iron borate/tetraboride hybrid as an efficient electrocatalyst for the oxygen evolution reaction - Ahmed, Tanbir; Pal, Santanu; Sinha, Nibedita; Das, Chandni; Roy, Poulomi (Dalton Transactions, 2026)
The design of an effective electrocatalyst as a replacement for a conventional expensive electrocatalyst for facilitating the sluggish oxygen evolution reaction (OER) at the anode has been identified as an effective way to make hydrogen production economical. Herein, we have developed a unique combination of iron borate and iron tetraboride (Fe-BO/FeB) by a facile chemical reduction process. The optimum vanadium doping further led to the transformation of Fe-BO/FeB into an amorphous form, which is believed to be very beneficial for the OER mechanism. The developed electrocatalyst needs overpotentials of 215 mV and 256 mV in alkaline 1 M KOH electrolyte to achieve current densities of 10 and 100 mA cm-2, respectively, and it also shows stability over 48 h, maintaining a high current density of 200 mA cm-2. Enhanced performances were also confirmed by smaller activation energies for the optimized sample compared with a pristine electrocatalyst.

Chitosan and layered double hydroxide nanosheets composite-based triboelectric nanogenerators for energy harvesting and touch sensing applications - Chaturvedi, Ekta; Roy, Poulomi; Pal, Santanu; Hossain, Afrin; Ahuja, Mayank (ACS Applied Nano Materials, 2026)
The alarming coexistence of increasing energy demand and environmental concerns has raised the immediate need to find suitable alternative energy resources. This need drives the development of environment-friendly, highly efficient tribo electric nanogenerators (TENGs), which have already gained significant success in mechanical energy harvesting. However, it still possesses challenges like ultralow current, which restricts its extensive applications in the real world. This article proposed the innovative combination of advanced layered double hydroxides (LDH) as a nanofiller with sodium chloride ionic salt as a simple strategy to enhance the output current of biodegradable chitosan polymer-based triboelectric nanogenerators (CS-TENG). Polymer chitosan provides a flexible matrix with many active sites, while the addition of LDH effectively enhances the surface area and positively charged sites due to its inherently positively charged layered nanostructure. This combination, together with NaCl-induced ionization and enhanced interfacial polarization, leads to an overall increase in the output performance of TENG. The developed TENG generated an output voltage (V OC) and current (I SC) of 101.6 V and 55.42 mu A, respectively, with a maximum power density of 629.5 mW m-2 at an external load resistance of 10 K Omega. It had the capability to power small-scale electronics like a watch, a calculator, an alarm buzzer, etc. A touch-sensitive TENG-based door sensor was also developed, which was capable of lighting LEDs just by a simple push on the door. This work demonstrated a simple, promising method to explore the potential of environmentally friendly CS-based mechanical energy harvesters for practical applications.
Keywords: Chitosan; Composite; layereddouble hydroxides; touch sensing; triboelectric nanogenerators

Dynamic and resilient cobalt copper nitride and iron nitride heterostructure aided energy economic urea electrolysis in anion exchange membrane electrolyzer - Sinha, Nibedita; Das, Chandni; Er, Chen-Chen; Urkude, Rajashri R.; Pal, Santanu; Ghosh, Biplab; Chai, Siang-Piao; Roy, Poulomi (Small, 2026)
Urea oxidation reaction (UOR) is recognized for energy-efficient hydrogen production, which nonetheless requires a meticulously designed electrocatalyst with active sites for intermediates adsorption and gaseous products desorption to fully exploit its advantages. Herein, we design the heterostructure consisting of cobalt copper nitride and iron nitride (Co3CuN/FexNy) as an efficient and trifunctional electrocatalyst, which requires 1.35 VRHE, 1.55 VRHE, and 0.23 VRHE potentials to reach 100 mA cm-2 current density for UOR, oxygen evolution reaction (OER), and hydrogen evolution reaction (HER), respectively. Unlike the conventional UOR selective electrocatalyst, Co3CuN/FexNy not only facilitates the UOR -> OER switching but also shows self-regulatory ability in UOR <-> OER. The Density Functional Theory (DFT) study explained that while Co3CuN promoted the adsorption of CO(NH2)2 and H2O, FexNy facilitated CO2 and N2 desorption, resulting in accelerated UOR and HER kinetics. The electrocatalyst also demonstrated outstanding performance in a urea-coupled AEM electrolyzer with about 20% of power saving and great electrolyzer efficiency, further highlighting its potential for industry-relevant applications.
Keywords: AEM electrolyzer; heterostructured electrocatalyst; reversible adaptability; urea oxidation; Water oxidation

Energy efficient electrophoretic coatings of MXene multilayers for enhanced corrosion resistance and tribological performances - Chaturvedi, Ekta; Bapanapalle, Chandra Obulesu; Pal, Santanu; Roy, Poulomi; Mandal, Nilrudra (Surface & Coatings Technology, 2026)
Surface wear, friction and corrosion have always been among major challenges faced by industries globally which cause significant economic and energy losses yearly. The recent emergence of two dimensional (2D) MXenes in tribology as protective coatings is noteworthy due to their layered structure, tuneable properties, easy to shear ability, and capability of forming anti-corrosion wear resistant tribo-films. In this work, multiple layers of Ti3C2Tx MXene coatings were applied on stainless steel (SS) substrates via energy electrophoretic deposition (EPD) process at low voltage of 5 V to enhance tribology and anti-corrosion behaviour of substrates. The tribological performance was investigated by rotating ball-on-disk tribometry at 5 N load with rotating velocity and radius of 500 RPM and 3 mm respectively. The effect of multiple coating layers on microstructure and tribological performance was also investigated to optimize the coating thickness followed by the extensive characterization of MXene and developed coatings. Surface hardness and coating thickness increased proportionally with increase in number of coating layers resulting into the maximum values of 311.39 HV and 3.25 mu m respectively. Tribological performance confirmed significant reduction in coefficient of friction (COF) and specific wear rate for MXene coated samples compared to uncoated SS substrates. Precisely, two coating layers' sample (MX2) demonstrated the best performance achieving approximate 41.3% and 65.7% reduction in coefficient of friction (COF) and wear rate, respectively. Further, corrosion studies also confirmed the protective role of MXene layers and great anti-corrosion behaviour of MX2 sample with 72.2% protection efficiency.
Keywords: Electrophoretic deposition; energy efficient; Multiple coating layers; Ti 3 C 2 T x MXene; Tribology